THERMOACOUSTIC REFRIGERATOR SYSTEM PERFORMANCE USING THE PVC (POLYVINYL CHLORIDE) STACK BY POWER INPUT VARIATION - Kharismawati, Indah (Jurnal Neutrino, 2017)
The thermoacoustic refrigerator is an innovative alternative and did not use substances that had a negative impact on the environment such as freon, but using air as the working substance. The materials used the refrigerator were easily obtained and the construction components were simple so that made this refrigerator was cheap, easy to make and easy to maintain. Stack was used in the thermoacoustic refrigerator system used PVC (Polyvinyl chloride) which is parallel cylindrical shape and diameter (1.50 ± 0.05) mm and length of 8 cm. Variations of loudspeaker input power that used were 20 watt, 30 watt, 40 watt, 50 watt and 60 watt. Variations of the input power that used to determine the effect of loudspeaker input power to decreasing temperature in the operating of the thermoacoustic refrigerator system using  PVC stack. From the result, loudspeaker input power influenced on the decreasing temperature that was 6.0 °C for 20 watts, 6.7 °C for 30 watts, 7.2 °C for 40 watts, 8.0 °C for 50 watts and 9.0 °C for 60 watts. From these results indicated optimum decreasing temperature depended on the amount of loudspeaker power that was directly proportional to the decreasing temperature obtained.